Pharmacological analysis and structure determination of 7-methylcyanopindolol–bound b1-adrenergic receptor - Sato, Tomomi; Baker, Jillian G.; Warne, Tony; Brown, Giles A.; Leslie, Andrew; Congreve, Miles; Tate, Christopher G. (ASPET, 2015)
Comparisons between structures of the b1-adrenergic receptor (AR) bound to either agonists, partial agonists, or weak partial agonists led to the proposal that rotamer changes of Ser5.46, coupled to a contraction of the binding pocket, are sufficient to increase the probability of receptor activation. (RS)-4-[3 (tertbutylamino)-2-hydroxypropoxy]-1H-indole-2 carbonitrile (cyanopindolol) is a weak partial agonist of b1AR and, based on the hypothesis above, we predicted that the addition of a methyl group to form 4-[(2S)-3 (tert-butylamino)-2-hydroxypropoxy]-7-methyl-1H-indole-2 carbonitrile (7-methylcyanopindolol) would dramatically reduce its efficacy. An eight-step synthesis of 7- methylcyanopindolol was developed and its pharmacology was analyzed. 7-Methylcyanopindolol bound with similar affinity to cyanopindolol to both b1AR and b2AR. As predicted, the efficacy of 7-methylcyanopindolol was reduced significantly compared with cyanopindolol, acting as a very weak partial agonist of turkey b1AR and an inverse agonist of human b2AR. The structure of 7-methylcyanopindolol–bound b1AR was determined to 2.4-Å resolution and found to be virtually identical to the structure of cyanopindolol-bound b1AR. The major differences in the orthosteric binding pocket are that it has expanded by 0.3 Å in 7-methylcyanopindolol–bound b1AR and the hydroxyl group of Ser5.46 is positioned 0.8 Å further from the ligand, with respect to the position of the Ser5.46 side chain in cyanopindololbound b1AR. Thus, the molecular basis for the reduction in efficacy of 7 methylcyanopindolol compared with cyanopindolol may be regarded as the opposite of the mechanism proposed for the increase in efficacy of agonists compared with antagonists.